Percutaneous Endoscopic Gastrostomy with T-Fasteners versus “Pull Technique”: Analysis of Complications - Castrillo, Alejandra; García-Martínez, Laura; Laín, Ana; Giné, Carlos; Díaz-Hervás, María; López, Manuel (European Journal of Pediatric Surgery, 2024)
Introduction The T-fasteners gastrostomy (T-PEG) has become increasingly popular over recent years as an alternative to the “pull-technique” gastrostomy (P-PEG). This study aimed to compare P-PEG and T-PEG complications.Materials and Methods A retrospective observational study of pediatric patients who underwent percutaneous endoscopic gastrostomy (PEG) placement. P-PEG was performed using the standard Ponsky technique and was replaced after 6 months by a balloon gastrostomy under sedation. T-PEG was performed using three percutaneous T-fasteners (that allow a primary insertion of a balloon gastrostomy). The balloon was replaced by a new one after 6 months without sedation. Complications were recorded.Results In total, 146 patients underwent PEG placement, 70 P-PEG and 76 T-PEG. The mean follow-up was 3.9 years (standard deviation = 9.6). Age, weight, and associated comorbidities were comparable (p > 0.05). The overall complications were 17 (24.2%) in the P-PEG group and 16 (21.0%) in the T-PEG group (p > 0.05). P-PEG was associated with more sedation for button replacement (97 vs. 2.6% [p < 0.05]). P-PEG was associated with more early tube dislodgement during the first replacement (7.2 vs. 1.4% [p = 0.092]). Two of the five dislodged gastrostomies in the P-PEG group underwent laparotomy due to peritonitis, whereas the only dislodged gastrostomy in the T-PEG group was solved endoscopically. Altogether, P-PEG was associated with more complications that required urgent endoscopy, laparotomy, or laparoscopy (18.6 vs. 6.6% [p < 0.05]).Conclusions P-PEG was associated with more sedation, complications during first button replacement, and complications requiring urgent endoscopy, laparotomy, or laparoscopy compared with T-PEG.
Keywords: gastrostomy; postoperative complications; endoscopy